A Psychological Portrait of a Participant of the Unarmed Resistance - Masiulionytė , Asta (Genocidas ir rezistencija, 2015)
The article provides a new approach, which allows analysing the history of the unarmed resistance within the context of its active participants. With the emphasis on personal experience and the analysis of its subjective evaluation, a psychological portrait (in a broad sense) of a participant of the unarmed resistance is identified. The aim of the article is to draw a psychological portrait of a participant of the unarmed resistance based on individual experience of political and religious unarmed resistance by its participants and subjective assessment of this experience in both the Soviet period and the period of independent Lithuania. In order to achieve this aim, the following objectives are implemented : 1) analysis of the circumstances for involvement in the unarmed anti-Soviet resistance, types of involvement, and subjective evaluation of the involvement by the participants themselves; 2) clarification of the trends in the attitudes of the participants in the unarmed anti-Soviet resistance towards their activities within the context of their experience of various encounters with the Soviet offensive; 3) exploration of the key aspects in the experience concerning persecution, searches, interrogations, and enforcement of sentences that reveal the most important traits of the person’s character and their dynamics; 4) research of the trends of the consistency in personality of the participants in the unarmed anti-Soviet resistance within the context of the independent Lithuania; 5) comparison of the psychological portraits of the participants of religious and political unarmed resistance in the Soviet period and the period of independent Lithuania. Based on the research, it may be concluded that the involvement in the unarmed anti-Soviet resistance is related to the models of such behaviour in the closest environment, which affected the main directions of resistance activities, their communal nature and attitudes towards individual anti-Soviet resistance. Trends in subjective assessment of these activities – most clearly manifested in the experience in labour camps and exile and associated with the formation, ascertaining, maintenance and defence of the individual system of values – were determined by direct interaction with the activities of the Soviet security services. The wish to foresee and control the actions of the opposition or unfavourable situations, permanent questioning of the social status of the opposition, and suspicion and mistrust, which are not generalised more broadly, are elements of the psychological portrait best revealed in the direct contact with the interrogation procedures of the Soviet security services, court proceedings and imprisonment. Portraits of the participants of the unarmed religious resistance reveal their more favourable attitude towards security personnel and giving meaning to their prison experience manifest in their interpersonal relations in a general sense, within the context of evaluation of their personality and their relationship with the world.